Social Media Addiction and Personality: A Review of Research - Viktor P. Sheinov (Peoples' Friendship University of Russia (RUDN University), 2021)
Social networks are taking up more and more place in the daily life of modern people, becoming an integral part of our existence. At the same time, the role of social networks is constantly growing along with the rapid growth in the number of their active users. As online interaction for many has become more used than face-to-face communication, social networks have begun to seriously affect the way of life, communication, interests and psychology of people. The use of social networks is growing exponentially and has covered more than a third of the worlds population; therefore, researchers from different countries are actively studying social networks. Considerable empirical data has been accumulated that requires generalization and understanding, which is the purpose of this review. We found positive links between social media addiction and depression, anxiety, stress, neuroticism, emotional problems, low self-esteem, cyber-victimization, physical health problems, mental disorders, loneliness, procrastination, smartphone and internet addiction, and infidelity in relationships. Negative links were revealed between social media addiction and life satisfaction, academic performance of schoolchildren and students, labor productivity and commitment to the organization of its employees, social capital, and age. The main reason for social media addiction is the need for communication, and women are generally more active in social networks than men. This review provides only those links of social media addiction that have been established in a number of studies conducted in different countries. The presented results were obtained abroad using foreign language questionnaires that determine social media addiction. The lack of such a reliable and valid tool among Russian-speaking psychologists has become a serious factor hindering the conduct of similar domestic research. With this in view, the author developed a specially designed social media addiction questionnaire.